CRYPTO ASSET TRENDS IN INDONESIA: NEW CHALLENGES TO INDONESIAN REGULATIONS - Lewiandy Lewiandy (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2022)
Cryptocurrency started its boom in Indonesia in 2013 and ever since, its popularity has soared in the community, especially among younger generations. Most enthusiasts agree that it is a captivating investment instrument due to its high return in the past years. The covid-19 pandemic strike, which led to series of lockdowns, plays a major role in echoing the digital asset’s popularity. The rapid growth of the asset’s adoption invites questions of regulation necessity and the role of related regulators. This writing addresses those questions and, in the end, this paper finds that the regulators need to identify the economic problems rise with the existence of the crypto assets and regulate sufficiently to ensure the innovation is not halted due to overregulation. This writing uses a juridical-normative research method with a case approach. Regulations made by the Government as the regulator are needed in order to realize protection, legal certainty and harmony in regulating investment activities and payments with cryptocurrency.